WAVES PROGRAM An investigation experience in the cultures of children and young people from Colombia. - Manjarrés, María Elena; Mejía, Marco Raúl (Revista Universidad de Guayaquil, 2013)
The construction of a civil and democratic culture in Science, Technology and Innovation is a central matter to the current development of our countries, to face the way since our current world, inequality and inequities take plce, and are generated by these matters of knowledge, technology, new languages, information, communication and innovation; In this sense, it is important to incorporate these matters from a very early age, with this purpose, the Waves Program Colciencias, has developed a Pedagogic Strategy (IEP), to build from the infancy, an approach to Science in a close and nice way, from a perspective which shapes the learning approaches : Situated, Collaborative, Problem-based and Critical Investigation, with an axis of cultural negotiation and dialogue of knowledge.